The Role of T Lymphocytes in the Pathogenesis of Paroxysmal Nocturnal Hemoglobinuria - Li, Chenyuan; Dong, Xifeng; Wang, Huaquan; Shao, Zonghong (Frontiers in Immunology, 2021)
Paroxysmal Nocturnal Hemoglobinuria (PNH) is an acquired hematopoietic stem cell genetic mutation disease that causes defective erythrocyte membrane hemolysis. Its pathologic basis is the mutation of the PIG-A gene, whose product is necessary for the synthesis of glycosylphosphatidylinositol (GPI) anchors, the mutation of PIG-A gene results in the reduction or deletion of the GPI anchor, which leads to the deficiency of GPI-anchored proteins (GPI-APs), such as CD55 and CD59, which are complement inhibitors. The deficiency of complement inhibitors causes chronic complement-mediated intravascular hemolysis of GPI-anchor deficient erythrocyte. PIG-A gene mutation could also be found in bone marrow hematopoietic stem cells (HSCs) of healthy people, but they have no growth advantage, only the HSCs with PIG-A gene mutation in PNH patients have this advantage and expand. Besides, HSCs from PIG-A-knockout mice do not show clonal expansion in bone marrow, so PIG-A mutation cannot explain the clonal advantage of the PNH clone and some additional factors are needed, thus, in recent years, many scholars have put forward the theories of the second hit, and immune escape theory is one of them. In this paper, we focus on how T lymphocytes involve in immune escape hypothesis in the pathogenesis of PNH.